2000
DOI: 10.1046/j.1471-4159.2000.0752464.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Cotransmission with Norepinephrine in the Sympathetic Nerve—Macrophage Interplay

Abstract: Abstract:The CNS modulates immune cells by direct synaptic-like contacts in the brain and at peripheral sites, such as lymphoid organs. To study the nerve-macrophage communication, a superfusion method was used to investigate cotransmission of neuropeptide Y (NPY) with norepinephrine (NE), with interleukin (IL)-6 secretion used as the macrophage read-out parameter. Spleen tissue slices spontaneously released NE, NPY, and IL-6 leading to a superfusate concentration at 3-4 h of 1 nM, 10 pM, and 120 pg/ml, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 40 publications
(57 reference statements)
1
49
0
1
Order By: Relevance
“…Only testing ex vivo splenic NK cytotoxicity revealed significantly higher NK cytotoxicity in HA animals. As this finding might well be the result of a differential in vivo stress response mediated via sympathetic neurotransmitters such as noradrenaline and neuropeptide Y (12,16,20,(22)(23)(24)30), to this end, we conclude that the postnatal stressors used in the present study do not primarily affect the immune system of the rats. However, such a conclusion cannot be comprehensive and might differ in the case of other postnatal experiences such as immune "stress" by early postnatal exposure to endotoxin (5,7,16).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Only testing ex vivo splenic NK cytotoxicity revealed significantly higher NK cytotoxicity in HA animals. As this finding might well be the result of a differential in vivo stress response mediated via sympathetic neurotransmitters such as noradrenaline and neuropeptide Y (12,16,20,(22)(23)(24)30), to this end, we conclude that the postnatal stressors used in the present study do not primarily affect the immune system of the rats. However, such a conclusion cannot be comprehensive and might differ in the case of other postnatal experiences such as immune "stress" by early postnatal exposure to endotoxin (5,7,16).…”
Section: Discussionmentioning
confidence: 50%
“…IL-6 is known to be a potent activator of the HPA system and is secreted under stress conditions (29). The IL-6 release from macrophages is furthermore under tight control of the activity of the sympathetic nervous system and related neurotransmitters, which in turn are released by stress (30). However, because IL-6 levels do not differ prechallenge between groups and show under poststress circumstances only a significant decrease in MS and CO groups, these findings are not indicative for an activation of the HPA system by IL-6 but instead may hint to additional differences in the sympathetic response (30) in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Since CD26 cleaves the N-terminus of effector proteins and our data indicated that cleavage of SDF-1 was not a mechanism through which CD26 affects hematopoietic trafficking, we hypothesized that an alternative protein containing an N-terminal CD26 cleavage site is mechanistically involved. A systematic search of protein sequence databases for proteins containing putative CD26 recognition sites intriguingly identified the neurotransmitter NPY (26), a ligand with cognate receptors on monocytes, osteoblasts, stromal cells, and ECs and that has been shown to regulate immune cell and bone homeostasis (27)(28)(29)(30). In addition, recent studies suggest a role for NPY in the regulation of BM niche components and HSPC trafficking (31,32).…”
Section: G-csf Increases Ec Cd26 and Enhances Hspc Transendothelial Mmentioning
confidence: 99%
“…In the current study, we found that NPY, a small peptide that is produced by neurons of the central and peripheral nervous systems (23,38), was an important inhibitor of monocyte recruitment to the brain during retrovirus infection. Mice deficient in NPY were more susceptible to retrovirus-induced neurological disease.…”
Section: Discussionmentioning
confidence: 57%